The δ13C Value of Fingerstick Blood Is a Valid, Reliable, and Sensitive Biomarker of Sugar-Sweetened Beverage Intake in Children and Adolescents. Issue 1 (25th January 2018) - MacDougall, Carly R; Hill, Catelyn E; Jahren, A Hope; Savla, Jyoti; Riebl, Shaun K; Hedrick, Valisa E; Raynor, Hollie A; Dunsmore, Julie C; Frisard, Madlyn I; Davy, Brenda M
Abstract: Background: Reliance on self-reported dietary intake methods is a commonly cited research limitation, and dietary misreporting is a particular problem in children and adolescents. Objective indicators of dietary intake, such as dietary biomarkers, are needed to overcome this research limitation. The added sugar (AS) biomarker δ 13 C, which measures the relative abundance of 13 C to 12 C, has demonstrated preliminary validity in adults. Objective: The purpose of this investigation was to determine the comparative validity, test-retest reliability, and sensitivity of the δ 13 C biomarker to detect AS and sugar-sweetened beverage (SSB) intake using fingerstick blood samples in children and adolescents. Methods: Children (aged 6–11 y, n = 126, 56% male, mean ± SD age: 9 ± 2 y) and adolescents (aged 12–18 y, n = 200, 44% male, mean ± SD age: 15 ± 2 y) completed 4 testing sessions within a 3-wk period. Participants' height, weight, demographic characteristics, and health history were determined at the first session; 24-h recalls were obtained at each visit and fingerstick blood samples were collected at visits 1 and 3. Samples were analyzed for δ 13 C value using natural abundance stable isotope mass spectrometry. δ 13 C value was compared with dietary outcomes in the full sample, and in child and adolescent subgroups. t Tests and correlational analyses were used to assess biomarker validity and reliability, whereas logistic regression and area under the receiver-operator characteristic curve (AUC) were used to evaluate sensitivity. Results: Reported mean ± SD AS consumption was 82.2 ± 35.8 g/d and 329 ± 143 kcal/d, and SSB consumption was 222 ± 243 mL/d and 98 ± 103 kcal/d. Mean δ 13 C value was –19.65 ± 0.69‰, and was lower in children than in adolescents (–19.80 ± 0.67‰ compared with –19.56 ± 0.67‰, P = 0.002). δ 13 C values were similar across sessions (visit 1: –19.66 ± 0.68‰; visit 3: –19.64 ± 0.68‰; r = 0.99, P < 0.001) and were associated ( P < 0.001) with intake of total AS (grams, kilocalories: r = 0.29) and SSB (milliliters, kilocalories: r = 0.35). The biomarker was able to better discriminate between high and low SSB consumers than high and low AS consumers, as demonstrated by the AUC (0.75 and 0.62, respectively). Conclusions: The δ 13 C biomarker is a promising, minimally invasive, objective biomarker of SSB intake in children and adolescents. Further evaluation using controlled feeding designs is warranted. Registered at clinicaltrials.gov as NCT02455388.